Run baby run - Cruz, Nicky; Buckingham, Jamie (Orlando, Florida : Bridge-Logos, 1968)
This is the thrilling story of Nicky Cruz's desperate battle against drugs, alcoholism, and a violent environment, as he searched for a better way of life on the streets of New York City.
Keywords: Cruz, Nicky; Pentecostal converts -- United States -- Biography